Implementasi Peraturan Nagari Tambang Kabupaten Pesisir Selatan Nomor 3 Tahun 2023 Tentang Larangan Menangkap Ikan Di Sungai Menggunakan Bahan Beracun Berbahaya Dan Alat-Alat Listrik Oleh Wali Nagari Tambang Terhadap Masyarakat Yang Melanggar - Ayu Azura; Sarah Hilyatun Nisa; Daffa Beny Nursyid; Faruq Hatfan; Ikhsan; Muhammad Chavit Andriansyah; Aditya Pratama; Elwidarifa Marwenny (GLOBAL SCIENTS PUBLISHER, 2025)
In Nagari Tambang, Pesisir Selatan Regency, people often catch fish in the river using dangerous tools such as using laced materials and centrum tools, which can damage the river ecosystem in Nagari Tambang. Many losses are caused by catching fish in this way, it is clear that this way of catching fish does not provide any benefits. On the contrary, it causes environmental damage in the event that so far there has been a regulation that regulates at the Nagari level, namely the Nagari Tambang Regulation of South Pesisir Regency Number 3 of 2023 concerning the prohibition of fishing in rivers using toxic, hazardous materials and power tools. The problem limitations in this writing include the Implementation of the Regulation of Nagari Tambang, South Coastal Regency Number 3 of 2023 and the obstacles or obstacles faced by the Nagari Wali in implementing Nagari Tambang, South Coastal Regency Number 3 of 2023. To answer these problems, a type of normative jurisprudence research is used using a case approach and a statutory approach. So that the conclusions are obtained: 1) Nagari Tambang Regulation number 3 of 2023 prohibits toxic materials and centrum tools for fishing. However, its implementation is hampered by a lack of understanding and supervision; 2) Wali Nagari faces obstacles because many people do not understand the negative impact of using toxic materials to catch fish. The wali nagari has not maximally explained the Nagari Regulation to the entire community, especially in remote areas.